The basalts of Mare Frigoris. Issue 10 (9th October 2015) - Kramer, G. Y.; Jaiswal, B.; Hawke, B. R.; Öhman, T.; Giguere, T. A.; Johnson, K.
Abstract: This paper discusses the methodology and results of a detailed investigation of Mare Frigoris using remote sensing data from Clementine, Lunar Prospector, and Lunar Reconnaissance Orbiter, with the objective of mapping and characterizing the compositions and eruptive history of its volcanic units. With the exception of two units in the west, Mare Frigoris and Lacus Mortis are filled with basalts having low‐TiO2 to very low TiO2, low‐FeO, and high‐Al2 O3 abundances. These compositions indicate that most of the basalts in Frigoris are high‐Al basalts—a potentially undersampled, yet important group in the lunar sample collection for its clues about the heterogeneity of the lunar mantle. Thorium abundances of most of the mare basalts in Frigoris are also low, although much of the mare surface appears elevated due to contamination from impact gardening with the surrounding high‐Th Imbrium ejecta. There are, however, a few regional thorium anomalies that are coincident with cryptomare units in the east, the two youngest mare basalt units, and some of the scattered pyroclastic deposits and volcanic constructs. In addition, Mare Frigoris lies directly over the northern extent of the major conduit for a magma plumbing system that fed many of the basalts that filled Oceanus Procellarum, as interpreted by Andrews‐Hanna et al. (2014) using data from the Gravity Recovery and Interior Laboratory mission. The relationship between this deep‐reaching magma conduit and the largest extent of high‐Al basalts on the Moon makes Mare Frigoris an intriguing location for further investigation of the lunar mantle. Key Points: Most of Frigoris is filled with high‐Al basalts Frigoris' eruptive history was complex and spatially varied Mare Frigoris overlies a major magma conduit